Unhealthy sponsorship in sport: a case study of the AFL - Ainslie Sartori; Melissa Stoneham; Melinda Edmunds (Elsevier, 2018)
Abstract Objective: To analyse the presence of unhealthy sponsorship on Australian Football League (AFL) club websites and player uniforms. Methods: An audit of AFL club websites and playing uniforms identified sponsors and used a traffic light system to categorise sponsors. Food and beverage sponsors were classified as Red, Amber or Green using nutrient criteria. Alcohol sponsors were classified as Red. Gambling sponsors were classified as Red (wagering companies and casinos) or Amber (venues that provide gambling and other services). Sponsors promoting healthy lifestyle concepts were classified as Green. All other sponsors were classified as Other. Results: Unhealthy sponsorship on AFL club websites and player uniforms is extensive. All 18 clubs had at least one Red sponsor. Fifteen clubs were sponsored by alcohol companies. Five clubs featured Red sponsor logos on their playing uniforms. Twelve clubs had Green sponsors. No clubs displayed Green sponsors on their playing uniforms. Conclusions: This study identified that unhealthy sponsorship is prevalent on AFL club websites and playing uniforms. Implications for public health: Sponsorship offers companies an avenue to expose children and young people to their brand, encouraging a connection with that brand. The AFL could reinforce healthy lifestyle choices by shifting the focus away from the visual presence of unhealthy sponsorship, while taking steps to ensure that clubs remain commercially viable. Policy makers are encouraged to consider innovative health promotion strategies and work with sporting clubs and codes to ensure healthy messages are prominent.